Beslan Hope - Tsalikov, Vadim (Russia : Kosyrev-Nesterov, Mikhail, 2008)
On 1 September 2004 terrorists seized school No. 1 in Beslan. Nadezda Gurieva, a teacher of history, was among the hostages together with her three childern: Boris, Vera and Irina, only one of whom survived the attack.
Verzio Film Festival Submission
Verzio Film Festival Submission